Pemberdayaan Masyarakat selama Pandemik Covid-19 di RT 001/008 Bulakrejo Kecamatan Sukoharjo Kabupaten Sukoharjo - Agus Purwanto; Suwarto; Ratna Dewi Eskundari (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The Covid-19 pandemic has a negative impact, especially in the economic sector throughout the world, including in Indonesia, and in this activity is the RT community. 001/008 Bulakrejo Sukoharjo Regency. The purpose of this community service is to empower the community in RT 001/008, Bulakrejo Village, Sukoharjo District, Sukoharjo Regency during the Covid-19 pandemic. The method used in this service was the lecture and mentoring method. The material presented was the manufacture of ecoenzyme with raw materials in the form of fruit and vegetable waste. Initial observations of partners' conditions showed that the community in RT 001/008, Bulakrejo Village, Sukoharjo District, Sukoharjo Regency has not been able to make environmentally friendly ecoenzyme that can be economically useful, for example, can be used as plant biological fertilizer or fish feed. For this reason, further assistance was needed so that in making this ecoenzyme more acceptable to the community so that it can make more production and a wider market. The results of community service activities carried out three times showed that partner communities can practice making and harvesting ecoenzymes. Thus, it can be said that this activity succeeded in meeting its target.